2019
DOI: 10.1136/bmjopen-2018-026773
|View full text |Cite|
|
Sign up to set email alerts
|

Believe #metoo: sexual violence and interpersonal disclosure experiences among women attending a sexual assault service in Australia: a mixed-methods study

Abstract: ObjectivesSexual abuse is a strong predictor of future psychiatric problems. A more nuanced qualitative understanding of mental health outcomes, in the context of interpersonal responses from family members towards survivors after sexual abuse, may help to better inform prevention and interventions.DesignA mixed-methods approach included a qualitative timeline method to map and identify contextual factors and mediating emotional responses associated with mental disorder following sexual abuse.SettingParticipan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 47 publications
0
20
0
1
Order By: Relevance
“…For many survivors, exiting the abusive environment was difficult or unlikely. These women reported that family members appeared to ignore, normalize the abuse, or minimize the severity thereof (Crowley & Seery, 2001; Lorentzen et al, 2008; Rees et al, 2019; Testa et al, 1990; White, 2013) and accuse the victim of not knowing what they were talking about (Mayhall, 2014) or that they had misunderstood the event (Crowley & Seery, 2001). In some cases, the victims were told upon disclosure that it was too late to disclose or report the abuse (Ussher & Dewberry, 1995).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For many survivors, exiting the abusive environment was difficult or unlikely. These women reported that family members appeared to ignore, normalize the abuse, or minimize the severity thereof (Crowley & Seery, 2001; Lorentzen et al, 2008; Rees et al, 2019; Testa et al, 1990; White, 2013) and accuse the victim of not knowing what they were talking about (Mayhall, 2014) or that they had misunderstood the event (Crowley & Seery, 2001). In some cases, the victims were told upon disclosure that it was too late to disclose or report the abuse (Ussher & Dewberry, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Stigmatization and blaming the victim for abuse. Looking back at the responses to disclosure or discovery of sexual abuse, many behavior patterns of the NOSA were perceived as harmful in terms of stigmatizing and blaming reactions (Chien, 2005;Hunter, 2015;Rees et al, 2019;Winnett, 2012). Accusing the victim of the sexual abuse, or stating that the victim brought the abuse upon herself, is seen as a nonsupportive behavior (Gill & Harrison, 2019;Waller & Ruddock, 1993) and may result in future nondisclosure (Chien, 2005;Collin-Vézina et al, 2015), psychopathology (Waller & Ruddock, 1993), and negatively impact the victim's therapeutic process of recovery (Bagley & Young, 1999).…”
Section: Theme 2: Nonsupportive Behaviors Experienced During or After...mentioning
confidence: 99%
“…While changes in societal norms have led to an increase in disclosing sexual violence, most of it remains hidden. [24][25][26][27] The latest Crime Survey for England and Wales shows that around five in six victims (83%) did not report their experiences to the police with annual figures for non-reported episodes around 160 000. 28 Many do not disclose because of stigma, victim-blaming, secrecy and self-silencing and self-blame.…”
Section: Open Accessmentioning
confidence: 99%
“…32 Studies have reported an association between negative disclosure experiences and higher risk of onset of mental disorder, such as post-traumatic stress disorder. 33 34 If reactions to disclosure are critical in the recovery process, 27 it is important to consider what is meant by negative responses, and to consider how we create the space for 'safe' disclosures in health settings.…”
Section: Open Accessmentioning
confidence: 99%
“…The #MeToo campaign brought about a radical change of norms, with societies through #MeToo starting to see SH as a structural problem that needed to be taken seriously. The research on SH has also escalated in the wake of the campaign, with studies investigating the impact of #MeToo from the feminist, sociological, journalistic, legal, and medical perspective, including the impact on mental health outcomes (see e.g., Rees, Simpson, McCormack, Moussa, & Amanatidis, 2019;Wexler, Robbennolt, & Murphy, 2019).…”
Section: Introductionmentioning
confidence: 99%